Analysis Of Meaning And Poetic Devices In The Poem “The Soldier” By Rupert Brooke - Robby Satria; Mhd Johan; Ramanda Rizki (Prosiding, 2025)
This article analyzes the meaning and poetic devices of the poem "The Soldier" by Rupert Brooke toward the sacrafaction of British soldier in World War I. This research uses a qualitative method by applying a Formalistic Approach based on LG Alexander's theory. Data collection techniques are carried out through close reading and analyzed using content analysis to interpret the thematic and structural elements of the text. The findings show that this poem functions primarily to commemorate the war hero as a form of noble sacrifice for the homeland. This poem represents a romanticized form of patriotism, typical of early World War I literary works. The analysis identifies the use of one structural device (illustration), one meaning device (metaphor), and two sound devices: rhyme (with eight different patterns) and rhythm (with a consistent structure of six syllables). All of these devices collectively enhance the poem's beautiful verse and reflection of honor, legacy, and national devotion.